Comparative Study of the Effect of Ethanol Extract of Psidium Guajava Linn Leaves with Glibenclamide on Experimentally Induced Diabetes Mellitus in Rats (Delta Medical College Journal, 2017)
Background: Diabetes Mellitus is a major health problem not only in urban but also in the rural areas of Bangladesh. Regarding its treatment, a suitable drug is yet to be available which can permanently cure this disease. Over 400 traditional plants have been reported for the treatment of diabetes, but only a small number have received scientific and medical evaluation to assess their efficacy.Objective: The study was performed to compare the anti diabetic effect of Psidium guajava Linn leaves with an oral anti diabetic drug (Glibenclamide), in experimentally induced diabetic rats.Materials and method: The experiment was carried out in the department of Pharmacology & Therapeutics of Dhaka Medical College, Dhaka, Bangladesh from July 2012 to June 2013. Twenty four healthy rats of Long Evans Norwegian strain were divided into 4 groups (group A, B, C and D) comprising 6 rats in each. Group A (normal control) received standard rat food for 14 days. Diabetes was induced by administration of Alloxan 120 mg/kg/body weight in group B, C and D. Group B (diabetic control group) was given standard rat food. Group C and D was treated with ethanol extract of Psidium guajava leaves 100 mg/kg body weight and Glibenclamide 1.5 mg/kg/day orally respectively. Total duration of the experiment was 15 days.Results: Administration of ethanol extract of Psidium guajava leaves in group C and Glibenclamide in group D produced a significant reduction (p